2020
DOI: 10.3390/en13174299
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Adsorbent Materials for Waste Energy Recovery

Abstract: Nowadays, waste thermal energy represents a huge quantity of energy that, in most cases, is unfortunately dispersed rather than recovered. Although it is well known that its recovery could result in a considerable impact reduction of human activities on the environment, it is still a challenging issue. In view of this, absorption chillers and heat pumps, based on the use of porous materials capable of reversibly adsorbing and desorbing water vapor, can be considered among the preferred systems to recover waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In particular, it has been proposed its encapsulation in a polymeric fibrous structure obtained via the electrospinning technique, that is a consolidated and industrially-relevant procedure. [24][25][26][27] Electrospun nanofibers have indeed numerous advantageous characteristics, including a high surface-to-volume ratio, porous structures, and tunable properties (chemical composition, morphology, and dimensions). [28,29] Moreover, it was reported that the integration of nanomaterials as electrodes can improve the sensitivity and reproducibility of electrochemical methods [30] and the detection of HMs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been proposed its encapsulation in a polymeric fibrous structure obtained via the electrospinning technique, that is a consolidated and industrially-relevant procedure. [24][25][26][27] Electrospun nanofibers have indeed numerous advantageous characteristics, including a high surface-to-volume ratio, porous structures, and tunable properties (chemical composition, morphology, and dimensions). [28,29] Moreover, it was reported that the integration of nanomaterials as electrodes can improve the sensitivity and reproducibility of electrochemical methods [30] and the detection of HMs.…”
Section: Introductionmentioning
confidence: 99%
“…The fields of application of electrospun nanostructures are numerous and wide, considering the high versatility of this kind of material. Manifold examples can be found in the environmental sector, such as in water treatment from contaminants [ 3 ], in the catalysis field, as improved catalysts [ 4 ], in biomedical applications, as medicament carriers [ 5 ], in sensor devices, as high reactive sensing materials [ 6 , 7 ], and in the sustainable exploitation of energy, as innovative adsorbents [ 8 , 9 , 10 , 11 ]. Moreover, the ES technique has been intensively employed for the design and fabrication of structured nanofibrous materials for energy conversion and storage devices, as well as dye-sensitized solar cells [ 12 ], fuel cells [ 13 ], lithium/sodium-ion batteries [ 14 ], supercapacitors [ 15 ], and electronic applications in general [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to contribute to decarbonization, today's energy sector is called to respond to a complex challenge: to simultaneously satisfy the recent energy needs of an increasingly large population, and to limit greenhouse gas emissions. On the one hand, there are promising solutions to supply the future energy demand, such as the recovery of waste energy and various technologies that produce power from renewable sources [1][2][3][4]. On the other hand, the last World Energy Outlook of the International Energy Agency explained what it means for the energy sector to achieve net-zero emission by 2050 (NZE2050) [5].…”
Section: Introductionmentioning
confidence: 99%